From Six-on-Six to Full Court Press : a Century of Iowa Girls' Basketball. - Beran, Janice A. (University of Iowa Press, 2008)
& Ldquo;From Six-on-Six to Full Court Press is a complete history of Iowa women & rsquo;s high school, college, and recreational basketball. Beran & rsquo;s exhaustive research ... covers legendary players and coaches, changes in rules, stats on Iowa girls & rsquo; high school records, alterations in playing styles and uniforms, along with the heart-stopping excitement of the state tournament. & rdquo; & mdash;Hoop Source.